Multiple stress tests and their effectiveness in managing bank risks (Entrepreneurship Journal for Finance and Business, 2020)
The global economy is going through multiple unexpected events and changes that will affect the banking sector, and therefore it is imperative to search for a tool that helps protect the banking institution and the banking sector, especially after the recent global financial crisis, as stress tests appeared, which in turn support management Risks in detecting banking risks before they arise, and therefore these tests give a dose of immunity to the banking community to protect it from expected and unexpected events. The research concluded that the banking stress test scenarios have partially affected the efficiency ratios that the banks have in the research sample, due to the durability of their financial suitability. Banks should apply the tests periodically and consider them as a shield that protects them from external influences.